2016
DOI: 10.2188/jea.je20150163
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Cost Estimation of a Baseline Survey for a Molecular Epidemiology Cohort Study: Collecting Participants in a Model Region in Japan

Abstract: BackgroundSome recent molecular epidemiology studies of the effects of genetic and environmental factors on human health have required the enrollment of more than 100 000 participants and the involvement of regional study offices across the country. Although regional study office investigators play a critical role in these studies, including the acquisition of funds, this role is rarely discussed.MethodsWe first differentiated the functions of the regional and central study offices. We then investigated the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…For instance, the National Children's Study (NCS) in the USA, a birth cohort study which has recruited at least 100 000 patients and has a follow-up period of 21 years estimated its costs to be 2.7 billion USD [13]. In Japan, Mishiro and colleagues [14] reported that the cost of a 4-year baseline survey was 153 In their calculations, they included costs for advertisement, patient recruitment, material fees, and equipment. Although the total cost may vary depending on the length and number of participants in the study, in the model survey they conducted in order to provide a close estimate of the required expenses, they calculated their total cost to be 14.4 million yen per year (136 814.40 CAD), and this only took into account the minimum number of items required to enrol 7400 participants.…”
Section: Challengesmentioning
confidence: 99%
“…For instance, the National Children's Study (NCS) in the USA, a birth cohort study which has recruited at least 100 000 patients and has a follow-up period of 21 years estimated its costs to be 2.7 billion USD [13]. In Japan, Mishiro and colleagues [14] reported that the cost of a 4-year baseline survey was 153 In their calculations, they included costs for advertisement, patient recruitment, material fees, and equipment. Although the total cost may vary depending on the length and number of participants in the study, in the model survey they conducted in order to provide a close estimate of the required expenses, they calculated their total cost to be 14.4 million yen per year (136 814.40 CAD), and this only took into account the minimum number of items required to enrol 7400 participants.…”
Section: Challengesmentioning
confidence: 99%
“…In the current issue of the Journal of Epidemiology , Mishiro et al 1 present a very careful and detailed cost estimation for a molecular epidemiology cohort study in a model region of Japan. Their approach and key points can be extended to other studies worldwide in order to rationalize planning and costs of molecular epidemiology cohort studies.…”
mentioning
confidence: 99%
“…There are two aspects, however, that require additional attention. First, the new cohort described by Mishiro et al, 1 which includes 7400 subjects, is relatively small for the subsequent analysis of most of its possible outcomes, despite its comprehensive and innovative data collection compared to cohorts defined in the 1980s and 1990s. 2 , 3 Thus, this dataset will inevitably need to be integrated with data from other cohort studies from Japan and other areas of the world; a similar project was recently developed within a network of cohort studies that included 23 European and 3 non-European studies (the Consortium of Health and Ageing), which includes over 680 000 elderly.…”
mentioning
confidence: 99%
See 1 more Smart Citation